American pietàs : visions of race, death, and the maternal - Tapia, Ruby C. (Critical American studies series., 2011)
In "American Pietas," Ruby C. Tapia reveals how visual representations of racialized motherhood shape and reflect national citizenship. By means of a sustained engagement with Roland Barthes's suturing of race, death, and the maternal in "Camera Lucida," Tapia contends that the contradictory essence of the photograph is both as a signifier of death and a guarantor of resurrection. Tapia explores the implications of this argument for racialized productions of death and the maternal in the context of specific cultural moments: the commemoration of Princess Diana in U.S. magaz.